Interplay of cis and trans mechanisms driving transcription factor binding and gene expression evolution. Issue 1 (December 2017) - Wong, Emily; Schmitt, Bianca; Kazachenka, Anastasiya; Thybert, David; Redmond, Aisling; Connor, Frances; Rayner, Tim; Feig, Christine; Ferguson-Smith, Anne; Marioni, John; Odom, Duncan; Flicek, Paul
Abstract Noncoding regulatory variants play a central role in the genetics of human diseases and in evolution. Here we measure allele-specific transcription factor binding occupancy of three liver-specific transcription factors between crosses of two inbred mouse strains to elucidate the regulatory mechanisms underlying transcription factor binding variations in mammals. Our results highlight the pre-eminence ofcis -acting variants on transcription factor occupancy divergence. Transcription factor binding differences linked tocis -acting variants generally exhibit additive inheritance, while those linked totrans -acting variants are most often dominantly inherited.Cis -acting variants lead to local coordination of transcription factor occupancies that decay with distance; distal coordination is also observed and may be modulated by long-range chromatin contacts. Our results reveal the regulatory mechanisms that interplay to drive transcription factor occupancy, chromatin state, and gene expression in complex mammalian cell states. "Variation in the noncoding regulatory sequences in the genome plays important roles in human disease and evolution. Here, the authors use F1 mouse hybrids to shed light on the regulatory mechanisms mediating transcription factor binding, chromatin state and gene expression in mammalian cells."